Victoria & Albert [videorecording (DVD)] - Erman, John, 1935-; Hamilton, Victoria, 1971-; Firth, Jonathan; Rigg, Diana; Suchet, David; Hawthorne, Nigel; Ustinov, Peter; Pryce, Jonathan; Redman, Joyce, 1915-2012 (New Video, 2001)
The moving romantic story of two lovers who create an intimate private world amidst the pomp and politics of the court of St. James. This epic miniseries shows us a Victoria that we have never seen before--not the staid and stately old matron cloaked in black--but a young, passionate, sensual Victoria who takes command of the throne and falls head over heels in love with the dashing German prince who will father her six children.